(untitled) (Heritage, 2021)
Marx did not deal explicitly with the theory of international relations but these relations were the part of the study of society and state. Marx put in the centre of his analysis economic activity and saw conflicts among peoples as the result of class struggle but not as the anarchical structure of international system itself. He also saw conflicts in the imperialistic structure of international system, which is the result of the lack of demand with national states. Marx put in the second place the relations of balance and power so as to put the individual in the first place. All this was the result of individualism and humanism. In that sense, Marx will be considered as the precursor of critical theories of society and international relations. Marx did not think of the establishment of peaceful relations among states by means of collective security since that system was not developed at his time. That system was realized by means of balance of power at international congresses and conferences. For Marx, the only way to reach peace was through dictatorship of proletariat by conquering economic and political power. The main critic of Marx comes from Habermas as neomarxist. He did not want to make a break with Marxism but to adapt it to new circumstances. It was the same as Marx critic of Hegel – to turn his dialectics upside down and reveal in that mystic layer rational core.